Physicochemical, microbiological, and sensory evaluation of kefir produced from goat milk containing Lacticaseibacillus casei AP and/or oat milk during storage - WULANSARI, Putri Dian; WIDODO, Widodo; SUNARTI, Sunarti; NURLIYANI, Nurliyani (Food Science and Technology, 2023)
This study combined the probiotic properties of Lacticaseibacillus casei AP with the prebiotic properties of oats to improve kefir products. Lacticaseibacillus casei AP, oat milk, or both were added to goat milk kefir. Physicochemical properties, microbiological evaluation, and sensory evaluation were done over the course of 14 days. The result showed that adding Lacticaseibacillus casei AP and oat milk together had positive (non-opposing) effects on the physicochemical, microbiological, and sensory properties of the kefir product until the end of shelf life. Compared to the control group, the viscosity of kefir increased by two times (13,630 vs. 6,716 mPa). The viscosity of goat milk that had been mixed with Lacticaseibacillus casei AP and oat milk and stored for 14 days also got thicker by 44%. Overall, Lacticaseibacillus casei AP and oat milk can be added to kefir simultaneously over time to improve its qualities.